Neurologial Interpretations and the Information in the Cognitive Pupillary Response - O’Neill, W. D.; Zimmerman, S. (Methods of Information in Medicine, 2000)
It has been known for 70 years that the human pupil dilates when a person responds to a cognitive task. Further, it is known that parasympathetic pupillary innervation decreases with raised attention state while sympathetic innervation increases. But the information the pupil transmits during elevated attention states about such neurological dynamics and a quantitative measure of this information have defied statistical modelling. Now we describe experiments using a short-term memory task called an acoustic impulse test in which the pupillary dynamics in response to random acoustic impulses are recorded with a high resolution (0.01mm) pupillometer with the result that parasympathetic and sympathetic pupillary dilation components are quantifiable, as is the information transmitted by these components.
Keywords: Neurology; Cognition; Pupil Dilation